City slickers [videorecording (DVD)] - Ganz, Lowell, 1948-; Mandel, Babaloo; Crystal, Billy; Stern, Daniel, 1957-; Kirby, Bruno, 1949-2006; Wettig, Patricia; Slater, Helen; Palance, Jack, 1919-2006 (Contemporary classics, 2001)
Comedy about three men friends who are going through mid-life crises. They decide that the answer to their malaise is a fantasy vacation out West where they can play cowboy on a cattle drive.